Síntese e caracterização estrutural de polialetos e compostos zwitteriônicos derivados de diteluretos de diarila - Silva, Felipe Dornelles da (2016)
The present work describes the synthesis and structural elucidation of ten new tellurium halide starting from diaryl ditellurides (aryl group = 2-piridine or N,N-dimethylbenzilamine). The compounds and starting material had their structures elucidated with monocrystal X ray diffraction and as an additional analysis another technique was used like infrared spectroscopy, Raman spectroscopy, 1H and 125Te Nuclear Magnetic Resonance and elemental analysis. Different methodologies were used to get tellurium II and tellurium IV compounds due the tellurium atom versatility which it behaved like neutral molecules and zwitterionic molecules (molecules that have an internal positive and negative charge). The compounds showed Te∙∙∙X secondary bonds or Te∙∙∙X and X∙∙∙X interactions (X = halogen atom) due to lone electron pair around the tellurium atom localization and to the tellurium-halogen affinity. In the solid state, these bonds make the compounds show a supramolecular arrangements which can be a pseudo-dimeric or pseudo-polymeric and it depends of the halogen atom attached to the tellurium atom.